Hypertrophic Cardiomyopathy in the Era of Targeted Therapy: The Role of Cardiac Myosin Inhibitors, Contemporary Sudden Cardiac Death Risk Stratification, and the Importance of Differential Diagnosis — A Narrative Review - Parda, Julia; Bundyra, Jakub; Janik, Dominika; Gańska, Oliwia Zuzanna; Sochocka, Agata; Zapart, Zuzanna; Martyna Szepietowska; Nowicka, Nina; Sikorska, Alicja; Mian, Emil (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Hypertrophic cardiomyopathy (HCM) is a common genetic myocardial disease characterized by unexplained left ventricular hypertrophy, phenotypic heterogeneity, and a clinical course ranging from asymptomatic presentation to heart failure, atrial fibrillation, ventricular arrhythmias, and sudden cardiac death. The aim of this narrative review was to summarize knowledge on HCM in the era of targeted therapy, with particular emphasis on cardiac myosin inhibitors, sudden cardiac death risk stratification, and the importance of differential diagnosis. Brief description of the state of knowledge: HCM should be regarded as a genetically mediated and phenotypically diverse disease rather than a single morphologic pattern. Phenotyping is essential because obstructive and non-obstructive forms differ in symptoms, prognosis, and treatment options. Cardiac myosin inhibitors, especially mavacamten and aficamten, represent mechanism-directed therapy targeting sarcomeric hypercontractility and have shown the greatest clinical benefit in symptomatic obstructive HCM. Sudden cardiac death prevention still requires individualized multivariable assessment integrating clinical markers, ambulatory rhythm evaluation, and cardiovascular magnetic resonance findings, particularly myocardial fibrosis. Differential diagnosis remains crucial because athlete’s heart, hypertensive remodeling, restrictive phenotypes, and infiltrative or metabolic phenocopies may mimic HCM but require different management. Summary (conclusions): Cardiac myosin inhibitors have become a major advance in symptomatic obstructive HCM, but their long-term role across all phenotypes remains to be defined. Contemporary management of HCM should combine precise phenotyping, substrate-oriented sudden cardiac death risk stratification, and careful differential diagnosis to support individualized care.